Meningkatkan Produktivitas Kerja melalui Pelatihan di Luar Ruangan di Lokasi Pembuangan Sampah Terpadu (TPST) Kelompok Masyarakat Berbek Makmur - Ilyas Indra; Siti Aisah; Efrizar Sunni; Handy Aribowo; Aris Adi Leksono (Komatika: Jurnal Pengabdian Kepada Masyarakat, 2026)
Work productivity is a crucial factor in improving organizational effectiveness, including at the Berbek Makmur Community Empowerment Centre (TPST Pokmas Berbek Makmur). Issues include suboptimal teamwork, work culture, and inter-personnel coordination. This community service activity aims to improve work productivity through outbound training. Implementation methods include field surveys, Training Needs Analysis (TNA), material dissemination, experiential learning-based outbound training, and evaluation through observation, reflective discussions, and questionnaires. The results of the activity indicate an increase in participants' understanding of teamwork, communication, work culture, and work productivity. Participants also demonstrated improved coordination, leadership, problem-solving, and collaboration skills during the training. The evaluation showed a positive response to the experiential learning method, which was deemed effective in increasing motivation and work skills. Thus, outbound training is an effective method for strengthening teamwork, building a work culture, and increasing work productivity at the Berbek Makmur Community Empowerment Centre (TPST Pokmas Berbek Makmur).